Theoretical Approaches to Nuclear Proliferation - Tarasov, K. S. (Vestnik MGIMO-Universiteta, 2015)
This article analyses discussions between representatives of three schools in the theory of international relations - realism, liberalism and constructivism - on the driving factors of nuclear proliferation. The paper examines major theoretical approaches, outlined in the studies of Russian and foreign scientists, to the causes of nuclear weapons development, while unveiling their advantages and limitations. Much of the article has been devoted to alternative approaches, particularly, the role of mathematical modeling in assessing proliferation risks. The analysis also reveals a variety of different approaches to nuclear weapons acquisition, as well as the absence of a comprehensive proliferation theory. Based on the research results the study uncovers major factors both favoring and impeding nuclear proliferation. The author shows that the lack of consensus between realists, liberals and constructivists on the nature of proliferation led a number of scientists to an attempt to explain nuclear rationale by drawing from the insights of more than one school in the theory of IR. Detailed study of the proliferation puzzle contributes to a greater understating of contemporary international realities, helps to identify mechanisms that are most likely to deter states from obtaining nuclear weapons and is of the outmost importance in predicting short- and long-term security environment. Furthermore, analysis of the existing scientific literature on nuclear proliferation helps to determine future research agenda of the subject at hand.